2021
DOI: 10.3892/ijo.2021.5251
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SNHG22 sponges miR‑128‑3p to promote the progression of colorectal cancer by upregulating E2F3

Abstract: The long non-coding RNA (lncRNA) small nucleolar RNA host gene 22 (SNHG22) has been reported as a crucial regulator in several types of human cancer. The present study evaluated the function and mechanism of SNHG22 in colorectal cancer (CRC) progression. SNHG22 expression was detected in colorectal adenoma, CRC tumor tissues (TTs) and adjacent non-cancerous tissues (ANTs) using reverse transcription-quantitative PCR (RT-qPCR). The biological behaviors of SNHG22 in CRC cell lines were explored in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Luan and colleagues recently reported that ALMS1-IT1 promoted the malignant progression of lung adenocarcinoma through AVL9-mediated activation of the cyclindependent kinase pathway (73). SNHG22 has been detected to be overexpressed and to act as an oncogene in multiple cancers, including CRC (74,75). Yao et al (75) revealed that SNHG22 promoted CRC cell growth, migration, and invasion through SNHG22/miR-128-3p/E2F3 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luan and colleagues recently reported that ALMS1-IT1 promoted the malignant progression of lung adenocarcinoma through AVL9-mediated activation of the cyclindependent kinase pathway (73). SNHG22 has been detected to be overexpressed and to act as an oncogene in multiple cancers, including CRC (74,75). Yao et al (75) revealed that SNHG22 promoted CRC cell growth, migration, and invasion through SNHG22/miR-128-3p/E2F3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG22 has been detected to be overexpressed and to act as an oncogene in multiple cancers, including CRC (74,75). Yao et al (75) revealed that SNHG22 promoted CRC cell growth, migration, and invasion through SNHG22/miR-128-3p/E2F3 axis. LINC00628 has been reported to inhibit the malignant progression of cancer through different mechanisms, such as binding to EZH2 to regulate the p57 or H3K27me3 level (76,77), and interacting with the promoter of LAMA3 or VEGFA (78,79).…”
Section: Discussionmentioning
confidence: 99%
“… 19 In addition, the density of infiltrated immune cells also has a crucial effect on patients’ prognosis in a variety of cancers; the presence of stromal cells and other immune cells have a strong correlation with the prognosis of multiple cancer. 37 , 38 , 39 Additionally, growing studies have shown that the high immune/stromal/estimate score is an independent prognostic factor(s) for poor overall survival of GC. 3 , 25 , 40 , 41 In our study, the overexpression of AFF3 was positively correlated with the high immune/stromal/estimate.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of miRNAs and E2F3 in regulating human cancers was proposed, and E2F3 was verified to exert a carcinogenic role in diverse tumors. 27 For instance, lncRNA SNHG22 could accelerate the development of colorectal cancer by sponging miR-128-3p and upregulating E2F3 expression, 28 and miR-573 suppressed cell progression in pancreatic cancer through regulating E2F3. 29 Likewise, E2F3 had elevated levels in esophageal squamous cell carcinoma (ESCC), and circ_0087378 deficiency blocked ESCC cell progression by enhancing E2F3 expression.…”
Section: Discussionmentioning
confidence: 99%